Ligand-controlled divergent asymmetric C(sp3)−H and C(sp3)−O insertion via vinyl cations - Li, Cui-Ting; Liu, Li-Gao; Li, Jia-Zheng; Dong, Hao-Xuan; Novikov, Roman A.; Wang, Ze-Shu; Hong, Xin; Zhou, Bo; Ye, Long-Wu (Nature communications, 2025)
The insertion of either C−H bond or C−O bond via bond cleavage has proven to be a very attractive strategy for the construction of C−C and C−O bonds in organic synthesis. However, such divergent catalytic asymmetric reactions for the selective formation of C(sp 3 )−H insertion and formal C(sp 3 )−O insertion products from the same precursors are rarely explored. Herein, we report a ligand-controlled divergent asymmetric C(sp 3 )−H insertion and formal C(sp 3 )−O insertion reaction via vinyl cations by a non-diazo approach, leading to the practical and atom-economical assembly of a range of chiral spiro and fused polycyclic pyrroles in generally moderate to excellent yields with generally excellent chemo- and enantioselectivities. Importantly, this protocol not only represents a rare example of successful ligand-controlled asymmetric divergent insertion reaction, but also constitutes an enantioselective 1,6-C−H insertion and an asymmetric carbenoid insertion into acetals via a non-diazo approach. Divergent catalytic asymmetric reactions for the selective formation of C(sp3)−H insertion and formal C(sp3)−O insertion products from the same precursors are rarely explored. Here, the authors report a ligand-controlled divergent asymmetric C(sp3)–H insertion and formal C(sp3)–O insertion reaction via vinyl cations, leading to the assembly of a range of chiral spiro and fused polycyclic pyrroles.